The genus Xiphinema Cobb, 1913 (Nematoda: Longidoridae) in Western Malaysia - Razak, Abdul Rahman; Loof, Pieter A. A.
A survey for Xiphinema species in Serdang, the Puchong area and the Cameron Highlands (Malaysia) yielded eleven species, of which one new, described hereunder as X.winotoi n.sp. It is close to X.radicicola.